Characterization of Radioactive and Rare Earth Elements in Heavy Minerals from River Sediments in Marau Region, Ketapang, West Kalimantan - Pratiwi, Fadiah; Rachael, Yoshi; Widodo, Widodo; Fauzi, Rachman; Madyaningarum, Nunik; Adimedha, Tyto Baskara; Indrastomo, Frederikus Dian; Sukadana, I Gde (Badan Riset dan Inovasi Nasional, 2024)
Alluvium deposits from the Kendawangan River located in Marau, Ketapang, West Kalimantan have been known for their radioactive and rare earth mineral potential. In this paper, heavy minerals taken from alluvium deposits will be characterized to determine the elemental distribution of uranium, thorium, and rare earth elements in each mineral and their mineralogical composition. The samples are taken by panning and prepared using the flotation method to obtain heavy mineral concentrates. Geochemical analysis was carried out using a Bruker M4 Tornado plus Micro-XRF and continued with mineralogical analysis using AMICS (Advanced Mineral Identification and Characterization System) software. It was found that the distribution of heavy minerals from the sand samples was dominated by manganoan ilmenite, ilmenite, rutile, zircon, magnetite, and monazite, as well as thorite, cassiterite, xenotime, allanite, and other minerals in small quantities. Uranium, thorium, and rare earth elements are found in monazite, thorite, xenotime, zircon, and allanite.